FRI0154 SAFETY AND EFFICACY OF FILGOTINIB IN PATIENTS AGED 65 YEARS AND OLDER: RESULTS FROM A PHASE 3 STUDY IN PATIENTS WITH ACTIVE RHEUMATOID ARTHRITIS AND PRIOR INADEQUATE RESPONSE OR INTOLERANCE TO BIOLOGICAL DMARDS (BDMARD-IR). (June 2019) - Kalunian, Kenneth; Gottenberg, Jacques-Eric; Genovese, Mark C.; Mozaffarian, Neelufar; Bartok, Beatrix; Matzkies, Franziska; Gao, Jie; Guo, Ying; Takeuchi, Tsutomu; Vlam, Kurt de; Walker, David
Abstract : Background: Filgotinib (FIL), an oral selective Janus kinase 1 (JAK1) inhibitor, demonstrated efficacy and safety vs placebo (PBO) in bDMARD-IR patients with active RA in a global phase 3 study (FINCH2, ClinicalTrials.gov NCT02873936 ). 1 Objectives: We performed a prespecified subgroup analysis of the safety and efficacy of FIL in patients aged ≥65 years vs <65 years in FINCH2 to understand FIL effects in older patients. Methods: 449 patients were randomized 1:1:1 to FIL 200 mg, FIL 100 mg, or PBO on a background of csDMARDs for 24 weeks. The primary efficacy endpoint was ACR20 response at week 12. Results: Of 448 patients who received ≥1 dose of study drugs, 113 (25.2%) were ≥65 years of age; baseline disease characteristics were similar for both age groups. Safety and efficacy parameters by age group are in Tables 1 and 2 . The most common treatment-emergent adverse events (TEAEs, by System Organ Class) category was infections and infestations; nasopharyngitis, upper respiratory tract infections, and bronchitis were the most common infections and infestations in the FIL arms in both age groups. There were no cases of opportunistic infection, active tuberculosis, malignancy, gastrointestinal perforation, or death. Efficacy outcomes were similar for both groups. Conclusion: Overall, older age was not associated with higher incidence of safety events (serious infections, herpes zoster, MACE occurred in the group <65 yrs) and efficacy was similar in older and younger bDMARD-IR patients with active RA. Reference: [1] MC Genovese, et al. ACR, 2018. Abstract L06. Disclosure of Interests: Kenneth Kalunian Grant/research support from: Gilead Sciences, Inc., Jacques-Eric Gottenberg Grant/research support from: Bristol-Myers Squibb, Grant/research support from: Bristol-Myers Squibb, Consultant for: Bristol-Myers Squibb, Lilly, Pfizer, Sanofi-Genzyme, UCB Pharma, Consultant for: Bristol-Myers Squibb, Eli Lilly, UCB, Sanofi-Genzyme, Pfizer, Mark C. Genovese Grant/research support from: Sanofi/Genzyme, Genentech/Roche, RPharm, Consultant for: Sanofi/Genzyme, Genentech/Roche, RPharm, Neelufar Mozaffarian Shareholder of: Gilead, Employee of: Gilead, Beatrix Bartok Shareholder of: Gilead, Employee of: Gilead, Franziska Matzkies Shareholder of: Gilead, Employee of: Gilead, Jie Gao Shareholder of: Gilead, Employee of: Gilead, Ying Guo Shareholder of: Gilead, Employee of: Gilead, Tsutomu Takeuchi Grant/research support from: Astellas Pharma Inc, Chugai Pharmaceutical Co, Ltd., Daiichi Sankyo Co., Ltd., Takeda Pharmaceutical Co., Ltd., AbbVie GK, Asahikasei Pharma Corp., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Eisai Co., Ltd., AYUMI Pharmaceutical Corporation, Nipponkayaku Co. Ltd., Novartis Pharma K.K., Grant/research support from: AbbVie, Asahi Kasei, Astellas, AstraZeneca, AYUMI, Bristol-Myers Squibb, Chugai, Daiichi Sankyo, Eisai, Eli Lilly Japan, Janssen, Mitsubishi Tanabe, Nippon Kayaku, Novartis, Pfizer Japan Inc, Taiho, Taisho Toyama, Takeda, Teijin, Grant/research support from: Astellas Pharma Inc., Bristol Myers Squibb, Chugai Pharmaceutical Co., Ltd., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Santen Pharmaceutical Co., Ltd., Takeda Pharmaceutical Co., Ltd., Teijin Pharma Ltd., AbbVie GK, Asahi Kasei Pharma Corp., Taisho Toyama Pharmaceutical Co., Ltd., SymBio Pharmaceuticals Ltd., Janssen Pharmaceutical K.K., Celltrion Inc., Nipponkayaku Co. Ltd., and UCB Japan, Consultant for: Astra Zeneca K.K., Eli Lilly Japan K.K., Novartis Pharma K.K., Mitsubishi Tanabe Pharma Co., Abbivie GK, Nipponkayaku Co.Ltd, Janssen Pharmaceutical K.K., Astellas Pharma Inc., Taiho Pharmaceutical Co. Ltd., Chugai Pharmaceutical Co. Ltd., Taisho Toyama Pharmaceutical Co. Ltd., GlaxoSmithKline K.K., UCB Japan Co. Ltd., Consultant for: AbbVie, Asahi Kasei, Astellas, AstraZeneca, AYUMI, Bristol-Myers Squibb, Chugai, Daiichi Sankyo, Eisai, Eli Lilly Japan, Janssen, Mitsubishi Tanabe, Nippon Kayaku, Novartis, Pfizer Japan Inc, Taiho, Taisho Toyama, Takeda, Teijin, Consultant for: Astra Zeneca K.K., Eli Lilly Japan K.K., Novartis Pharma K.K., Mitsubishi Tanabe Pharma Co., Asahi Kasei Medical K.K., AbbVie GK, Daiichi Sankyo Co., Ltd., Bristol Myers Squibb, and Nipponkayaku Co. Ltd., Speakers bureau: Astellas Pharma Inc., Bristol Myers Squibb, Chugai Pharmaceutical Co., Ltd., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Santen Pharmaceutical Co., Ltd., Takeda Pharmaceutical Co., Ltd., Teijin Pharma Ltd., AbbVie GK, Asahi Kasei Pharma Corp., Taisho Toyama Pharmaceutical Co., Ltd., SymBio Pharmaceuticals Ltd., Janssen Pharmaceutical K.K., Celltrion Inc., Nipponkayaku Co. Ltd., and UCB Japan, Speakers bureau: AbbVie, Asahi Kasei, Astellas, AstraZeneca, AYUMI, Bristol-Myers Squibb, Chugai, Daiichi Sankyo, Eisai, Eli Lilly Japan, Janssen, Mitsubishi Tanabe, Nippon Kayaku, Novartis, Pfizer Japan Inc, Taiho, Taisho Toyama, Takeda, Teijin, Speakers bureau: AbbVie GK., Bristol–Myers K.K., Chugai Pharmaceutical Co. Ltd., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Astellas Pharma Inc, Diaichi Sankyo Co. Ltd., Eisai Co. Ltd., Sanofi K.K., Teijin Pharma Ltd., Takeda Pharmaceutical Co. Ltd., Novartis Pharma K.K., Kurt de Vlam Consultant for: Pfizer Inc, Consultant for: Johnson & Johnson, David Walker: None declared